2020
DOI: 10.1002/jsfa.10386
|View full text |Cite
|
Sign up to set email alerts
|

Composition and biological effects of goldenberry byproducts: an overview

Abstract: Goldenberry is a wild fruit that has been widely used for centuries, mainly in folk medicine. Most studies of goldenberry have focused on the fruit, but new research has studied its byproducts, which were considered to be waste until recently. The main objective of our study was to systematize the published information regarding the composition of goldenberry byproducts (calyces, leaves, seeds, and pomace) and their effects on biological systems. Goldenberry byproducts contain minerals, amino acids, withanolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
3
17
0
1
Order By: Relevance
“…In general, the presence of TPC contributes to the AC of the berry (Nocetti et al, 2020). In the present work, the bagasse of the berries had the highest AC than pulp both in DPPH and ABTS (Table 1 Jakobek et al (2007) in elderberry from Croatia (100.16 μmol TE/gfw), and in goldenberry, 1.46 AE 0.04 μmol TE/gfw was founded, value lower than found by Ozturk et al (2017) in goldenberry from Turkey (6.05-5.14 μmol TE/gfw).…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the presence of TPC contributes to the AC of the berry (Nocetti et al, 2020). In the present work, the bagasse of the berries had the highest AC than pulp both in DPPH and ABTS (Table 1 Jakobek et al (2007) in elderberry from Croatia (100.16 μmol TE/gfw), and in goldenberry, 1.46 AE 0.04 μmol TE/gfw was founded, value lower than found by Ozturk et al (2017) in goldenberry from Turkey (6.05-5.14 μmol TE/gfw).…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 99%
“…This bagasse still contains a large amount of bioactive compounds of great interest to the food industry (V azquez-Gonz alez et al, 2020). In the case of goldenberry, it has been found that most studies have focused only on its properties, rather than on the by-products obtained from the industrial process (Nocetti et al, 2020). The manufacture of juices and derivatives of blueberry produces around 20-30 % of by-products that are discarded (Luchese et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La planta de uchuva se desarrolla como un semiarbusto semiperenne y su hábito de crecimiento es indeterminado, es decir, las fases vegetativas y reproductivas se traslapan (Ramírez, et al, 2013), llegando a alturas entre 1 y 1,5 m. Toda la parte aérea de la planta desarrolla una densa pubescencia, especialmente en las hojas, que son simples, corazonadas y alternas (Fischer & Melgarejo, 2020). Las flores solitarias desarrollan una corola tubular amarilla, en tanto que el cáliz que cubre el fruto durante todo su desarrollo consta de cinco sépalos persistentes (similares a hojas modificadas) (Nocetti, et al, 2020), de unos 4 a 5 cm de largo, los cuales protegen el fruto contra plagas, la luz UV, la lluvia, el granizo y las temperaturas bajas y se transforman en una cáscara translúcida a medida que el fruto alcanza su madurez (Fischer & Miranda, 2012), pues transfieren sus carbohidratos al fruto (Fischer, et al, 2015). El fruto de la uchuva es botánicamente una baya de color amarillo anaranjado cuando está maduro, un diámetro entre 1,25 y 2,5 cm y un peso entre 4 y 10 g, y contiene hasta 350 semillas (Fischer, et al, 2007;Fischer & Melgarejo, 2020).…”
Section: Introductionunclassified
“…The flowers are hermaphroditic with a yellow tubular corolla and are solitary, while the calyx with a cupuliform structure (Nocetti et al, 2020), consists of five persistent sepals (or modified leaves). These form a husk 4-5 cm long that encloses and protects the fruit (against pests, UV light, rain, hail and cold) until maturity.…”
mentioning
confidence: 99%